Cody

Problem 39. Which values occur exactly three times?

Solution 896738

Submitted on 27 May 2016 by Dennis Winston
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

Test Suite

Test Status Code Input and Output
1   Pass
x = [1 2 5 2 2 7 8 3 3 1 3 8 8 8]; y_correct = [2 3]; assert(isequal(threeTimes(x),y_correct))

row = 1 col = 14 M = 8 F = 4 row = 1 col = 10 Y = 0 0 0 0 0 0 0 0 0 0 Y = 0 2 0 0 0 0 0 0 0 0 Y = 0 2 0 0 0 0 0 0 0 0 Y = 0 2 0 2 0 0 0 0 0 0 Y = 0 2 0 2 0 0 0 0 0 0 Y = 0 2 0 2 2 0 0 0 0 0 Y = 0 2 0 2 2 0 0 0 0 0 Y = 0 2 0 2 2 0 3 0 0 0 Y = 0 2 0 2 2 0 3 0 0 0 Y = 0 2 0 2 2 0 3 3 0 0 Y = 0 2 0 2 2 0 3 3 0 0 Y = 0 2 0 2 2 0 3 3 0 3 Y = 0 2 0 2 2 0 3 3 0 3 Y = 2 2 2 3 3 3 r = 1 c = 6 y = 0 0 0 0 0 0 Y = 0 0 0 3 3 3 Y = 3 3 3 Y = 0 0 0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 y = 2 3

2   Pass
x = [1 1 1]; y_correct = [1]; assert(isequal(threeTimes(x),y_correct))

row = 1 col = 3 M = 1 F = 3 row = 1 col = 3 Y = 0 0 0 Y = 1 0 0 Y = 1 0 0 Y = 1 1 0 Y = 1 1 0 Y = 1 1 1 Y = 1 1 1 Y = 1 1 1 r = 1 c = 3 y = 0 0 0 Y = 0 0 0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 y = 1

3   Pass
x = [5 10 -3 10 -3 11 -3 5 5 7]; y_correct = [-3 5]; assert(isequal(threeTimes(x),y_correct))

row = 1 col = 10 M = -3 F = 3 row = 1 col = 10 Y = 0 0 0 0 0 0 0 0 0 0 Y = 5 0 0 0 0 0 0 0 0 0 Y = 5 0 0 0 0 0 0 0 0 0 Y = 5 0 -3 0 0 0 0 0 0 0 Y = 5 0 -3 0 0 0 0 0 0 0 Y = 5 0 -3 0 -3 0 0 0 0 0 Y = 5 0 -3 0 -3 0 0 0 0 0 Y = 5 0 -3 0 -3 0 -3 0 0 0 Y = 5 0 -3 0 -3 0 -3 0 0 0 Y = 5 0 -3 0 -3 0 -3 5 0 0 Y = 5 0 -3 0 -3 0 -3 5 0 0 Y = 5 0 -3 0 -3 0 -3 5 5 0 Y = 5 0 -3 0 -3 0 -3 5 5 0 Y = 5 -3 -3 -3 5 5 r = 1 c = 6 y = 0 0 0 0 0 0 Y = 5 0 0 0 5 5 Y = 5 5 5 Y = 0 0 0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 Y = Empty matrix: 1-by-0 y = -3 5